Discovering the Frontiers of Human-Robot Interaction Insights and Innovations in Collaboration, Communication, and Control - Vinjamuri, Ramana (Springer Nature Switzerland : Imprint: Springer, 2024)
XI, 493 p. 155 illus., 142 illus. in color.